Design of Photovoltaic Inverter Based on the Effect of Potential Induced Degradation for Solar Cells - YAO Ming; GUO Jijing (Kongzhi Yu Xinxi Jishu)
It described the mechanisms and the degradation mode of potential-induced degradation (PID) for solar cells. The special designs of photovoltaic inverter has been taken to reduce PID effect and improve photovoltaic generation’s efficiency of the system.